2007 IEEE International Conference on Acoustics, Speech and Signal Processing - ICASSP '07 2007
DOI: 10.1109/icassp.2007.366957
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Acoustic Maps to Determine Speaker Position and Orientation from a Distributed Microphone Network

Abstract: Acoustic maps created on the basis of the signals acquired by distributed networks of microphones allow to identify position and orientation of an active talker in an enclosure. In adverse situations of high background noise, high reverberation or unavailability of direct paths to the microphones, localization may fail. This paper proposes a novel approach to talker localization and estimation of head orientation based on the classification of Global Coherence Field (GCF) or Oriented GCF maps. Preliminary expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Six areas were randomly chosen inside the room, avoiding border areas. ͑Areas 1, 3,5,11,22,23,29,37,43,45,47, and 49 are border areas in Fig. 7.…”
Section: Best Array Selection By Individual Criteriamentioning
confidence: 98%
See 2 more Smart Citations
“…Six areas were randomly chosen inside the room, avoiding border areas. ͑Areas 1, 3,5,11,22,23,29,37,43,45,47, and 49 are border areas in Fig. 7.…”
Section: Best Array Selection By Individual Criteriamentioning
confidence: 98%
“…Using the same standard metrics of the SRP-PHAT orientation method, i.e., the average error, the ability of the system to correctly classify the source orientation within eight classes separated by 45°, and assuming correct classification error of Ϯ1 adjacent class, 51°, 30%, and 68% were obtained, respectively. Brutti et al 19,23 extended the GCF position localization method to consider the source orientation. The new method was named the oriented global coherence field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have focused on using distributed arrays in SSL and defining some spatial related factors to the localization algorithm [29,30,31]. Distributed networks of microphones have also been used to create acoustic maps based on the classification of a global coherence field or oriented global coherence field to identify position and orientation of a speaker [32]. The near-and far-field arrays of such a distributed network is utilized in the European Commission integrated project CHIL, "Computers in the Human Interaction Loop" project, to solve the problems of speaker localization and tracking, speech activity detection and distant-talking automatic speech recognition [33].…”
Section: Distributed Arraysmentioning
confidence: 99%
“…Although more computationally expensive, it was shown that they provide reliable results. In particular, when even the maximization of the "global coherence" fails, a suitable analysis and classification of the spatial map yields useful information to localize a speaker and determine his/her head orientation [8].…”
Section: Global Coherence Mapsmentioning
confidence: 99%